2020
DOI: 10.1038/s41598-020-58184-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Influences of Processing Conditions on the Properties of Spray Dried Chitosan-Tripolyphosphate Particles loaded with Theophylline

Abstract: polymer matrix as a result of the increased size of TH/Chitosan-TPP particles obtained from higher TPP to chitosan ratio, thereby increasing their encapsulation efficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…However, as shown in Figure 6 , the increase in inlet temperature favored the formation of shrunken-type microparticles due to a faster evaporation rate. Similar observations were previously made by other authors [ 38 , 40 ]. For instance, Wei et al [ 40 ] recently observed that the particle size increased when increasing the liquid flow-rate, whereas the number of indentations increased by increasing the inlet temperature, during the encapsulation of theopylline in STPP-cross-linked chitosan using spray drying.…”
Section: Resultssupporting
confidence: 93%
“…However, as shown in Figure 6 , the increase in inlet temperature favored the formation of shrunken-type microparticles due to a faster evaporation rate. Similar observations were previously made by other authors [ 38 , 40 ]. For instance, Wei et al [ 40 ] recently observed that the particle size increased when increasing the liquid flow-rate, whereas the number of indentations increased by increasing the inlet temperature, during the encapsulation of theopylline in STPP-cross-linked chitosan using spray drying.…”
Section: Resultssupporting
confidence: 93%
“…Spray drying is a technique in which drugs and polymer solutions, suspensions, or emulsions are atomized through a nozzle and injected into hot air (Wei et al, 2020 ) ( Figure 6 ). As the solvent rapidly evaporates, the atomized droplets are transformed into solid particles (Shi et al, 2020 ; Wei et al, 2020 ). The spray drying process usually includes four stages: atomization, droplet mixing with dry gas, solvent volatilization, and product separation, in which the technological conditions and parameters of the atomization process play a decisive role in the droplet size distribution (Ré, 2006 ; Liu et al, 2015 ; Deshmukh et al, 2016 ; Messa et al, 2020 ), such as the selection of atomizer, nozzle pressure, feed or air flow rate, etc (Bowey & Neufeld, 2010 ; Shi et al, 2020 ).…”
Section: Preparation Methods Of Plga Microspherementioning
confidence: 99%
“…Abu Fara et al [ 8 ] used roller compaction to improve CH powder flow qualities and to make its compression and compaction characteristics compatible for use in industrial pharmaceutical machines. Additionally, there are some on-going trials to extend the use of CH and CHS as excipients in a similar method followed in improving MCC powder flow using spray drying [ 6 , 18 ]. Such studies, show that CH is a suitable solid pharmaceutical excipient.…”
Section: Introductionmentioning
confidence: 99%